The Regulation of Brain Nucleoside Utilization - L. Ipata, Piero; Balestri, Francesco (Current Metabolomics, 2014)
The homeostatic regulation of intracellular purine and pyrimidine pools has long been studied at the level of de novo nucleotide synthesis. However, brain maintains the proper qualitative and quantitative nucleotide balance by salvaging preformed nucleosides, imported from blood stream, rather than by de novo synthesis from simple precursors. The main salvage enzymes are the nucleoside-kinases, catalyzing the ATP mediated phosphorylation of nucleosides in their 5’-position. Salvaged nucleoside-monophosphates are then either further phosphorylated, or converted back to nucleosides by a set of 5’-nucleotidases. This poses the following problem: why are nucleosides produced from nucleosidemonophosphates, to be converted back to the same compounds at the expense of ATP? As discussed in this article, the quantitative and qualitative intracellular balance of brain purine and pyrimidine compounds is maintained i) by the intracellular interplay between the rates of nucleoside-kinases and 5’-nucleotidases, ii) by the relative rates of the inward and outward nucleoside transport through equilibrative and concentrative transport systems, iii) by the metabolic cross-talk between extracellularly exported nucleoside-triphosphate breakdown and the intracellular process of nucleoside-triphosphate salvage synthesis.
Keywords: Substrate cycles